Transferência reversa de conhecimento: estudo de caso entre uma subsidiária de país emergente e matriz em país desenvolvido - Giusti, Fernanda Cristina de Souza (Universidade do Vale do Rio dos Sinos, 2017)
Knowledge is an important source of competitive advantage and the main reason for the internationalization of companies. With the increasing interest of multinational companies (MNEs) in developing countries, evidenced by the increase in Foreign Direct Investment (FDI) in emerging nations, the acquired subsidiaries increase their strategic importance in the network of the multinational, since it has knowledge that allows the creation of competitive advantages. (ANDERSSON; DELLESTRAND; PEDERSEN, 2014). However, the reverse knowledge transfer, which flows from the subsidiary to the parent company, still presents unique challenges in the management of MNCs. (FOSS; HUSTED; MICHAILOVA, 2010). The present study aimed to analyze the process of reverse transfer of a knowledge generated in a Brazilian subsidiary and transferred to headquarter of a North American corporation. Through a single case study, the data were collected in documentary analysis, in situ observation and interviews with several managers in the United States headquarter and in the Brazilian and Mexican subsidiaries. Afterwards, the data were triangulated with the technique of content analysis. The results indicate the existence of a reverse transfer of knowledge in a non-explicit way, corroborating the studies in this area. However, during the process mapping, singularities were perceived in the case studied, such as the motivation and effort of the subsidiary to be recognized by the knowledge generated and the characterization of actors involved in the process that are not addressed in the literature.
Keywords: Transferência de conhecimento; Transferência reversa de conhecimento; Relação matriz-subsidiária; Multinacional em mercados emergentes; Knowledge transfer; Reverse knowledge transfer; Headquarter-subsidiary relation; Multinational in emerging markets; ACCNPQ::Ciências Sociais Aplicadas::Administração